Talking Teacher Education: Factors Impacting on Teacher Education for Indigenous People. Issue 1 (22nd January 2009) - Reid, Jo-Anne; Santoro, Ninetta; Crawford, Laurie; Simpson, Lee
Abstract: In this paper we report the findings of research that has examined, from first-hand accounts, the career pathways of Indigenous Australians who have studied to become teachers. We focus on one key aspect of the larger study: the nature and experience of initial teacher education for Indigenous student teachers. Elsewhere we have reported on aspects of their subsequent working lives in teaching or related fields. We focus here on participants' talk about teacher education, particularly with reference to the factors that have impacted positively and negatively on their identity formation as "Indigenous" students and teachers. As a research collective that comprises Aboriginal and non-Aboriginal teacher educators, and in the context of increased emphasis on university access following the Federal Review of Higher Education, we argue that it is time for government, universities and schools to listen and learn from this talk. In particular, we highlight in our participants' accounts the persistence of three longstanding and interrelated factors that continue to impact on the success or inadequacy of teacher education for Aboriginal people i.e., the presence and nature of financial, emotional and academic support in university and school settings.